Non-covalent Tough Hydrogels for Functional Actuators. Issue 8 (2016) - Fu, Jun; Gao, Guorong; Sun, Yuanna
ABSTRACT: Tough and responsive hydrogels have recently attracted great research interests for potential applications in artifical muscles, soft robotics, and actuators, etc. This paper overviews our recent progresses in the design and synthesis of hydrogels with very high strength and toughness, and actuators based on these hydrogels. Inorganic nanospheres, nanorods, and nanosheets are exploited as multi-functional crosslinkers to adsorb or bond with hydrophilic chains, leading to hydrogels with very high strength, toughness, fatigue resistance, and/or self-healing. Introduction of functional groups including ionic monomers and amino groups results in hydrogels reponsive to pH, ionic strength and electric field. Besides, ionoprinting has been used to change local crosslink density based on reversible chelating/decomposition of metal ions with functional groups. This process is rapid and thus enables reversible and rapid actuation of hydrogel devices. Our studies will further aim to develop sophiscated devices by assembling hydrogel actuators.